Peran Komunikasi Organisasi dalam Meningkatkan Loyalitas Karyawan McDonalds The Park Solo Baru - Islamnudin, Rifky Uchwa; Wangi, Maya Sekar; Widiyowati, Estu (Solidaritas, 2024)
The aim of this research is to find out the role of organizational communication in an effort to increase employee loyalty at McDonalds' The Park Solo New. Informer determination technique using purposive sampling. Data collection using interview and documentation techniques. Triangulation is the triangulation of sources and methods. Data analysis techniques use qualitative analysis. The new Park Solo consists of upward communication, downward communication and horizontal communication. Downward communication is a form of instruction and also supervision of its employees, upwards communication is the form of employee participation to the organization while horizontal communications is the coordination in the execution of work at The Park Solo New. Organizational communication plays a role in increasing employee loyalty.